Developing a composite index of spatial accessibility across different health care sectors: A German example. Issue 2 (February 2016) - Siegel, Martin; Koller, Daniela; Vogt, Verena; Sundmacher, Leonie
Abstract : Highlights: We develop an integrated index of health care accessibility. We consider potential cross-border utilization and limited substitutability of different healthcare sectors. Urban areas have better healthcare accessibility than rural areas. This pattern persists when taking a holistic view across different healthcare sectors. The index may contribute to an integrated capacity planning. Abstract: The evolving lack of ambulatory care providers especially in rural areas increasingly challenges the strict separation between ambulatory and inpatient care in Germany. Some consider allowing hospitals to treat ambulatory patients to tackle potential shortages of ambulatory care in underserved areas. In this paper, we develop an integrated index of spatial accessibility covering multiple dimensions of health care. This index may contribute to the empirical evidence concerning potential risks and benefits of integrating the currently separated health care sectors. Accessibility is measured separately for each type of care based on official data at the district level. Applying an Improved Gravity Model allows us to factor in potential cross-border utilization. We combine the accessibilities for each type of care into a univariate index by adapting the concept of regional multiple deprivation measurement to allow for a limited substitutability between health care sectors. The results suggest that better health care accessibility in urban areas persists when taking a holistic view. We believe that this new index may provide an empirical basis for an inter-sectoral capacity planning.